COMPUTER TEACHERS’ AWARENESS OF VIRTUAL REALITY FOR INSTRUCTIONAL PURPOSE IN KWARA STATE - Aderonke Kofo Soetan; Amos Ochayi Onojah; Adenike Janet Aderogba; Omotayo Olabo Obielodan; Olanrewaju Sulaimon Ganiyu; Micheal Ayodele Fakomogbon (Indonesian Journal of Learning and Instruction, 2020)
Virtual reality is an emerging technology designed to provide interaction between a user and artificially generated environments. However, most teachers in Nigeria are not aware of how virtual reality can be widely used for educational purposes. The study investigated (i) awareness of teachers towards the use of virtual reality for instructional purpose and influence of gender and experience on teachers’ awareness of virtual reality for instructional purpose. Descriptive survey research design was adopted for this study. 360 computer teachers were sampled from secondary schools across Kwara State with the use of researchs-developed questionnaire. The findings established that Virtual Bicycle and 3D Map world are the virtual reality facilities which most respondents are of aware for instructional purpose; and there was no significant difference between teachers’ awareness of VR for instructional purpose based on gender and experience. It was thus recommended that seminars and training could also be organised for teachers on how to use VR to facilitate their teaching in and outside the classroom environment.Keywords: awareness; computer teachers; virtual reality; gender; experience; instructional purposes.